Quantification of cell density in rat Achilles tendon: development and application of a new method. - Couppé, Christian; Svensson, René; Heinemeier, Katja; Thomsen, Emilie; Bayer, Monika; Christensen, Lise; Kjær, Michael; Magnusson, S.; Schjerling, Peter (Histochemistry & Cell Biology, 2017)
Increased tendon cell nuclei density (TCND) has been proposed to induce tendon mechanical adaptations. However, it is unknown whether TCND is increased in tendon tissue after mechanical loading and whether such an increase can be quantified in a reliable manner. The aim of this study was to develop a reliable method for quantification of TCND and to investigate potential changes in TCND in rat Achilles tendons in response to 12 weeks of running. Eight adult male Sprague-Dawley rats ran (RUN) on a treadmill with 10° incline, 1 h/day, 5 days/wk (17-20 m/min) for 12 weeks (which improved tendon mechanical properties) and were compared with 11 control rats (SED). Tissue-Tek-embedded cryosections (10 µm) from the mid region of the Achilles tendon were cut longitudinally on a cryostat. Sections were stained with alcian blue and picrosirius red. One blinded investigator counted the number of tendon cell nuclei 2-3 times in three separate regions of the mid longitudinal tendon sections with fields of 390 μm × 280 μm. Unpaired t tests were used for the statistical analysis (mean ± SE). Typical Error % for replicate counts was 5.5 and 14 % coefficient of variation for the three regions. There was no difference in TCND between running rats versus control rats (nuclei per image (≈10 μm): RUN, 152 ± 9; SED, 146 ± 8, p = 0.642). This new method provided reproducible quantification of TCND. There was no difference in TCND despite improvements in tendon mechanics, which suggests that cell number is not a major cause for altered tendon mechanical properties with loading.